О фауне инфузорий водоемов бассейна Северского Донца - Кравченко, В.М. (Вестник зоологии, 1969)
211 species of infusoria of the orders Holotricha, SpirotricKa, Peritricha and the subclass Suctoria were found during the investigation of 75 different reservoirs of the Seversky Donets'basin. Out of them 21 species were marked first for the USSR, 110—for the Ukraine, 76 — for the Kharkov region. The species composition of the infusoria in the reservoirs of the Seversky Donets basin considerably differs from that of the Leningrad region and the Moldavian SSR. The fauna of infusoria in different reservoirs has its peculiarities. The greatest quantity of the infusoria species was detected in rivers, the least one — in streams and temporary reservoirs. The most original fauna by its composition was found in the temporary reservoirs, it almost has no original features in the streams.